2015
DOI: 10.1097/hcr.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Equations to Estimate Peak Oxygen Uptake and Work Rate From a 6-Minute Walk Test in Patients With COPD in a Clinical Setting

Abstract: There is poor to moderate agreement between measured peak (Equation is included in full-text article.)o2 and peak work rate and estimations from equations that use 6MWT distance, and the use of the estimated values for prescription of aerobic exercise intensity would result in large error. Equations estimating peak (Equation is included in full-text article.)o2 and peak work rate are of low utility for prescribing exercise intensity in pulmonary rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This study shows that, as already reported other sedentary populations [5][6][7][8] This study is part of a wider study investigating the effects of exercise training at the level of VT 1 and one of the fi ndings was that VO 2max declined by 16.4%, over 1 year without training while this decline was prevented by training. Although it is well accepted that diabetes is a progressive disease [23], such a rapid decline highlights the "vicious circle" of a sedentary lifestyle in chronic diseases [24], and characterized by rapid deterioration even at the stage of disease where patients are comparatively healthy.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study shows that, as already reported other sedentary populations [5][6][7][8] This study is part of a wider study investigating the effects of exercise training at the level of VT 1 and one of the fi ndings was that VO 2max declined by 16.4%, over 1 year without training while this decline was prevented by training. Although it is well accepted that diabetes is a progressive disease [23], such a rapid decline highlights the "vicious circle" of a sedentary lifestyle in chronic diseases [24], and characterized by rapid deterioration even at the stage of disease where patients are comparatively healthy.…”
Section: Discussionsupporting
confidence: 83%
“…Since it has been widely studied and validated in chronic pathologies associated to sedentary lifestyles [5][6][7][8], it appears to be logically more and more employed in diabetes studies [9]. However, the basis for this use was until recently poorly documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This estimation of maximal power is associated with an average error of 22%±18%. 15 To compensate for the variability of this estimation, the intensity of the initial CWRET will be adjusted if the TLim is less than 5 min or more than 15 min, and the intensity of work will be increased or decreased by 20%. Initially, the aim of the test will be to accustom the patient to the instructions.…”
Section: Methods and Analysismentioning
confidence: 99%
“…All participants complete a baseline cardiorespiratory fitness test (week 0) using a maximal effort cycling protocol to measure VO 2 max, used in order to prescribe the relative exercise intensity. 48 49 The specific protocol comprises a 10W increase in workload every 1 min, starting at 40W. This testing is performed with standard equipment for indirect calorimetry (Parvo Medics, Salt Lake City, Utah) in an incremental protocol until exhaustion (respiratory exchange ratio >1.10, heart rate ±10/min predicted MHR, ratings of perceived exertion 17; in 6–20 ratings) on a recumbent bike.…”
Section: Additional Outcomesmentioning
confidence: 99%